Distribution, transformation, and toxic effects of the flame retardant tetrabromobisphenol S and its derivatives in the environment: A review - Xu, Xuehui; Zhang, Yuexin; Huang, Honglin; Chen, Jiafeng; Shi, Tailong (The Science of the total environment, 2024)
As widely used alternative brominated flame retardants, tetrabromobisphenol S (TBBPS) and its derivatives have attracted increasing amounts of attention in the field of environmental science. Previous studies have shown that TBBPS and its derivatives easily accumulate in environmental media and may cause risks to environmental safety and human health. Therefore, to explore the environmental behaviours of TBBPS and its derivatives, in this paper, we summarized relevant research on the distribution of these compounds in water, the atmosphere, soil and food/biota, as well as their transformation mechanisms (biological and nonbiological) and toxic effects. The summary results show that TBBPS and its derivatives have been detected in water, the atmosphere, soil, and food/biota globally, making them a ubiquitous pollutant. These compounds may be subject to adsorption, photolysis or biological degradation after being released into the environment, which in turn increases their ecological risk. TBBPS and its derivatives can cause a series of toxic effects, such as neurotoxicity, hepatotoxicity, cytotoxicity, thyrotoxicity, genotoxicity and phytotoxicity, to cells or living organisms in in vitro and in vivo exposure. Toxicological studies suggest that TBBPS as an alternative to TBBPA is not entirely environmentally friendly. Finally, we propose future directions for research on TBBPS and its derivatives, including the application of new technologies in studies on the migration, transformation, toxicology and human exposure risk assessment of TBBPS and its derivatives in the environment. This review provides useful information for obtaining a better understanding of the behaviour and potential toxic effects of TBBPS and its derivatives in the environment. [Display omitted] •The distribution of TBBPS and its derivatives in water, atmosphere, soil and food/biota were reviewed.•TBBPS and its derivatives were transformed biologically and abiotically in the environment.•TBBPS and its derivatives could induce hepatotoxicity, endocrine toxicity, neurotoxicity, cytotoxicity to organisms.•The future research directions for TBBPS and its derivatives are proposed.